Análisis de la política hídrica en México. El caso del municipio de Morelia Michoacán - Sauno Guzmán, Sureymi (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Given the main water problems that arise in the municipality of Morelia Michoacán, of which the most priority is; the scarcity and pollution of the Rio Grande and Chiquito, which function as a wastewater discharge, there is currently no proposal for a solution, which is why it is very important to apply well-established public water policies that allow prevention, These and more problems continue to increase. The purpose is to obtain good functioning, through public policies to promote and improve the quality of life of the citizens of the municipality of Morelia, and subsequently to different municipalities and states of our country, as well as implement future prevention strategies. It seeks to provide information that will be useful to develop and implement a public water policy in Morelia, with the laws that channel positive actions and restrict negative ones, for which legal, administrative, technical, economic and social instruments will be used for their implementation. corresponding application, and according to the information obtained, in reports, analysis, studies, objectives, agreements, strategic plans, allocation of resources and monitoring, to achieve balance and equity between the social, economic and environmental aspects. It is better to have a context that generates and guarantees compliance, and is expressed through a legal structure, that is, they are based on laws, norms, agreements, and benefit all people, to conserve the biodiverse heritage of the municipality of Morelia and achieve a orderly growth and according to the potential vocations of the citizens of the Municipality, and likewise that they are fulfilled, that is why water must be treated fundamentally as a social and cultural good, and not only as an economic good, which is how it can be seen at the moment.

Ante los principales problemas de agua que surgen en el municipio de Morelia Michoacán, de los cuales los más prioritarios son; la escasez y la contaminación del rio grande y chiquito, que funcionan como descarga de agua residual, actualmente no se cuenta con alguna propuesta de solución, por lo que resulta de mucha importancia aplicar políticas públicas del agua, bien establecidas, que permitan prevenir, que estos y más problemas sigan en aumento. El propósito es obtener un buen funcionamiento, a través de políticas públicas para favorecer y mejorar la calidad de vida, de los ciudadanos del municipio de Morelia, y posteriormente a diferentes municipios y estados de nuestro país, así como implementar las estrategias de prevención a futuro. Se busca proporcionar información que será útil para desarrollar e implementar una política pública del agua en Morelia, con las leyes que encauzan las acciones positivas y restringen las negativas, para las cuales se recurrirá a instrumentos jurídicos, administrativos, técnicos, económicos y sociales para su correspondiente aplicación, y conforme a la información obtenida, en informes, análisis, estudios, objetivos, acuerdos, planes estratégicos, asignación de medios y seguimiento, para lograr el equilibrio y equidad entre lo social, lo económico y lo ambiental. Es mejor tener un contexto que genere y garantice su cumplimiento, y se exprese mediante una estructura legal, es decir se sustentan en leyes, normas, acuerdos, y beneficiar a todas las personas, para conservar el patrimonio biodiverso del municipio de Morelia y lograr un crecimiento ordenado y acorde a las vocaciones potenciales de los ciudadanos del Municipio, y así mismo que se cumplan, es por eso que el agua debe tratarse fundamentalmente como un bien social y cultural, y no sólo como un bien económico, que es como se ve actualmente.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2023-1627; Ciencias políticas; Agenda pública; Agua potable; Sustentable; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16783